Intradural Disk Herniation Mimicking a Spinal Tumor: Radiologic Imaging, Pathogenesis, and Operative Management - Daisuke Tateiwa; Ryoji Yamasaki; Rinsei Tei; Yasushi Shin; Kenta Ariga; Kenji Hayashida; Eiji Wada (Case Reports in Orthopedics)
Intradural disk herniation (IDH) is a rare condition, occurring more often at the L4-5 level. We examined a case of an IDH at the L1-2 level mimicking an intradural spinal tumor. A 71-year-old woman with a long history of backache and pain radiating down the left leg was admitted to our hospital with the worsening of these symptoms. Magnetic resonance imaging and computed tomographic myelography demonstrated an intradural mass at the L1-2 level. Given the radiologic findings and the location of the mass, the preoperative differential diagnosis centered on intradural spinal tumors. Dural incision was performed using a surgical microscope to resect the mass. Contrary to our expectation, the diagnosis made during the surgery was IDH. Despite advances in imaging techniques, IDH could not be definitively diagnosed preoperatively. The pathogenesis of IDH remains unclear. In our patient, the ventral dural defect was smooth and round, and the dural tissue around the defect was thickened. These intraoperative findings suggested that the patient’s IDH resulted not from an acute new event but from a chronic process. We recommend dural incision using a surgical microscope for treating IDH because it provides a clear visual field.